THE IMPLEMENTATION OF ORAI APPLICATION IN TEACHING SPEAKING TO SENIOR HIGH SCHOOL STUDENTS - Tatang Saripudin (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2020)
In this era, speaking is really important for us because English is international language. In Indonesia, most of students especially in senior high school are difficult to speak up because they are shy and they are not confident. In this era there are a lot of media for teaching, but sometimes people do not know how to use it. Many media can help teacher to teach speaking, like application in our phone. Orai is one of applications that can help teacher in teaching speaking and this application is easy to use. Therefore this study is aimed at finding out: (1) The implementation of Orai application in teaching speaking; (2) The obstacles of using Orai application in teaching speaking; and (3) Students’ response in implementing Orai application. This is a descriptive qualitative study. This study was conducted in a Senior High School in Cianjur, the participants were an English teacher and twenty eight students of the eleventh grade at social class 1 selected purposively. The instruments on this research cover classroom observation, guided interview, and open ended questionnaire. The data from those instruments were transcribed and categorized accordingly. The findings show that the teacher applied several main steps in using Orai application: introducing the application, explaining the purpose of Orai application in teaching speaking, downloading and installing the application, practicing speaking by using Orai application and getting feedbacks from the application. The application helps the teacher by giving instant feedbacks such as clarity, total filler words, pausing score, and energy score. In this case the students were enthusiastic when the teacher implemented the application. However, the students face some obstacles in speaking by using Orai application: the signal should be stable and good, students less confidence, students’ low mastery on operating Orai application and students confusion because the feedback was full in English. Even though there were some obstacles, the students gave a good response because the students more active and enthusiastic when the teacher implemented Orai application in teaching speaking.   Keywords: Speaking skill, Orai application, Senior High School, qualitative, obstacles